2020
DOI: 10.1007/s00421-020-04490-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long-term athletic training on muscle morphology and tendon stiffness in preadolescence: association with jump performance

Abstract: Purpose Evidence on training-induced muscle hypertrophy during preadolescence is limited and inconsistent. Possible associations of muscle strength and tendon stiffness with jumping performance are also not investigated. We investigated the thickness and pennation angle of the gastrocnemius medialis muscle (GM), as indicators for potential muscle hypertrophy in preadolescent athletes. Further, we examined the association of triceps surae muscle–tendon properties with jumping performance. Methods Eleven untra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 118 publications
(161 reference statements)
1
4
0
1
Order By: Relevance
“…In addition, the biological maturation (Tanner stages) of the gymnasts was not examined, which could affect the results of the asymmetries, since it is known that the observed age of the participants is crucial for biological maturation. In the studies with observed isometric knee strength or CMJ parameters, the sample size varied but is comparable to our study Pentidis et al, 2019Pentidis et al, , 2020Thompson et al, 2017), while other studies had larger sample sizes (Bencke et al, 2002;Ceroni et al, 2012;Hall et al, 2016;Karagianni et al, 2020;Kinser et al, 2008;Markström et al, 2019). However, the results showed good reliability for all observed parameters.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In addition, the biological maturation (Tanner stages) of the gymnasts was not examined, which could affect the results of the asymmetries, since it is known that the observed age of the participants is crucial for biological maturation. In the studies with observed isometric knee strength or CMJ parameters, the sample size varied but is comparable to our study Pentidis et al, 2019Pentidis et al, , 2020Thompson et al, 2017), while other studies had larger sample sizes (Bencke et al, 2002;Ceroni et al, 2012;Hall et al, 2016;Karagianni et al, 2020;Kinser et al, 2008;Markström et al, 2019). However, the results showed good reliability for all observed parameters.…”
Section: Discussionsupporting
confidence: 81%
“…The study by Bencke et al (2002) compared CMJ height between gymnasts, swimmers, handball and tennis players and a study by compared CMJ height between gymnasts and a control group after the intervention. They found no significant differences in jump height between the observed groups, unlike the studies by Pentidis et al, (2019Pentidis et al, ( , 2020 that observed gymnasts and a control group of non-athletes, and the studies (Dallas, Kirialanis & Mellos, 2014;Dallas et al, 2019;Hall et al, 2016;Karagianni et al, 2020;Kinser et al, 2008) conducted on a gymnast and a control group after the intervention. The studies reported significant differences in jump height between the observed groups.…”
Section: Discussionmentioning
confidence: 82%
“…Despite this, there are some studies reporting positive associations between jump height and muscle architecture in athletes belonging to different sports [57][58][59]. In contrast, a recent study observed a significant relationship between Achilles tendon stiffness and jumping height in children practising artistic gymnastic [61]. Similarly, measures of muscle dimensions have been associated with parameters related to sports performance.…”
Section: Testing Athletes' Status With Respect To Performance-related Factors and Their Response To Trainingmentioning
confidence: 99%
“…Latihan kekuatan memerlukan periodesasi yang tepat, terdapat dua periodesasi, pertama linier (satu puncak) kedua bergelombang dengan beberapa puncak, kedua cara ini sama sama efektif untuk meningkatkan kekuatan, tetapi jika dibandingkan antara kedua metode ini metode satu puncak lebih efektif (Evans, 2019). Latihan senam dalam jangka yang panjang berkorelasi terhadap kekuatan otot, untuk atlet ternyata kekuatan otot lebih besar 35% dan untuk tinggi lompatan berbeda 36% (Pentidis et al, 2020) Disimpulkan bahwa stretch training tidak berpengaruh terhadap hipertrofi otot, tetapi stretch training yang dilakukan dengan memberikan beban kepada otot yang mengakibatkan otot berkontraksi akan memiliki pengaruh (Nunes et al, 2020).…”
Section: Pembahasanunclassified